KEWENANGAN MPR SEBAGAI LEMBAGA TINGGI NEGARA - Silitonga, Marudut Parulian; Wijayati, Ani; H, Andree Washington (Fakultas Hukum Universitas Kristen Indonesia, 2024)
Every high state institution in the Republic of Indonesia has the authority contained in the 1945 Constitution of the Republic of Indonesia. The authority granted by the constitution is a binding authority for high state institutions. The strengths and weaknesses of the authority of high state institutions influence the constitutional law system in Indonesia. Authority between high state institutions is a reflection of the checks and balances in the democratic system in Indonesia. The People's Consultative Assembly (MPR) of the Republic of Indonesia has become the highest state institution after the 1945 Constitution of the Republic of Indonesia, where this institution is called the highest state institution. As a high state institution, the MPR has the authority to amend and enact the constitution. The MPR's authority is also stated in Law No. 17 of 2014 concerning MD3 in article 4, which is more ceremonial in nature. Strengthening the authority of the MPR is very necessary as a high state institution to create balance and corrections between state institutions. It is hoped that the MPR institution will not be a complementary high institution in the Indonesian constitutional system.